2015
DOI: 10.3389/fphys.2015.00330
|View full text |Cite
|
Sign up to set email alerts
|

Tendon Vasculature in Health and Disease

Abstract: Tendons represent a bradytrophic tissue which is poorly vascularized and, compared to bone or skin, heal poorly. Usually, a vascularized connective scar tissue with inferior functional properties forms at the injury site. Whether the increased vascularization is the root cause of tissue impairments such as loss of collagen fiber orientation, ectopic formation of bone, fat or cartilage, or is a consequence of these pathological changes remains unclear. This review provides an overview of the role of tendon vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
93
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 61 publications
1
93
0
Order By: Relevance
“…Accumulating evidence suggests that tendon tissues generally possess more vessels than commonly believed, although they are recognized as a poorly vascularized tissue type [70]. Moreover, rich capillary networks in human embryonic tendons are found to promote tendon tissue formation and maturation [71].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that tendon tissues generally possess more vessels than commonly believed, although they are recognized as a poorly vascularized tissue type [70]. Moreover, rich capillary networks in human embryonic tendons are found to promote tendon tissue formation and maturation [71].…”
Section: Discussionmentioning
confidence: 99%
“…During the early stage of healing after tendon injury and rupture, there is an initial, robust vascular response with increased VEGF expression, then predictably drops off with time [57]. Several studies also reported that hypervascularization was observed after initial implantation, which diminished to native tendon levels at a late stage of healing [31, 37]. These results indicate that neovascularization is a natural healing process and may be essential for long term survival of grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Although tendon is recognized as a poorly vascularized tissue type, it generally possesses more vessels than commonly believed [31]. A rich capillary network is found in human embryonic tendon, although both cellularity and vessel density decrease in matured human tendon [32].…”
Section: Introductionmentioning
confidence: 99%
“…The Achilles tendon is viscoelastic, which defines time-dependent functional characteristics that describe the recruitment of collagen fibers (creep), molecular interactions and fluid exudation (stress relaxation), and energy up-take (hysteresis). Tendon cells (tenoblasts and some mesenchymal stem cells 10 ) reside between the strands of collagen fibers where they can sense physical stimuli, like fluid flow, and change their synthetic activities accordingly 11 . The response to this mechanosensation means that the tissue composition, structure and biomechanics adapts to the local mechanical environment 11,12 .…”
Section: Introductionmentioning
confidence: 99%